In Planta Recognition of a Double-Stranded RNA Synthesis Protein Complex by a Potexviral RNA Silencing Suppressor - Okano, Yukari (American Society of Plant Biologists, 2014)
RNA silencing plays an important antiviral role in plants and invertebrates. To counteract antiviral RNA silencing, most plant viruses have evolved viral suppressors of RNA silencing (VSRs). TRIPLE GENE BLOCK PROTEIN1 (TGBp1) of potexviruses is a well-characterized VSR, but the detailed mechanism by which it suppresses RNA silencing remains unclear. We demonstrate that transgenic expression of TGBp1 of plantago asiatica mosaic virus (PlAMV) induced developmental abnormalities in Arabidopsis thaliana similar to those observed in mutants of SUPPRESSOR OF GENE SILENCING3 (SGS3) and RNA-DEPENDENT RNA POLYMERASE6 (RDR6) required for the trans-acting small interfering RNA synthesis pathway. PlAMV-TGBp1 inhibits SGS3/RDR6-dependent double-stranded RNA synthesis in the trans-acting small interfering RNA pathway. TGBp1 interacts with SGS3 and RDR6 and coaggregates with SGS3/RDR6 bodies, which are normally dispersed in the cytoplasm. In addition, TGBp1 forms homooligomers, whose formation coincides with TGBp1 aggregation with SGS3/RDR6 bodies. These results reveal the detailed molecular function of TGBp1 as a VSR and shed new light on the SGS3/RDR6-dependent double-stranded RNA synthesis pathway as another general target of VSRs.